The water mite family Aturidae Thor (Acari: Hydrachnidia) from Ghana, with the description of twelve new species - Smit, Harry (Zootaxa, 2016)
Eleven new aturid species are described from Ghana: (Aturinae) Aturus ghanaensis n. sp., Subaturus spathulasetus n. sp., Subalbia elongata n. sp., (Axonopsinae) Albaxona wanjakliensis n. sp., Axonopsis kintampo n. sp., Brachypodopsis indistincta n. sp., Hexaxonopsis rectimarginata n. sp., H. subtruncata n. sp., Javalbia coalescens n. sp., J. indentata n. sp., Paraxonopsis latihumerosa n. sp. and Pseudaxonopsalbia ghanensis n. sp. New records are given for five species of the genera Albia, Kongsbergia, Paraxonopsis and Subaxonopsalbia.